2021
DOI: 10.1001/jamanetworkopen.2021.30479
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Rates of COVID-19–Associated Hospitalization, Intensive Care Unit Admission, and In-Hospital Death in the United States From March 2020 to February 2021

Abstract: IMPORTANCE Racial and ethnic minority groups are disproportionately affected by COVID-19.OBJECTIVES To evaluate whether rates of severe COVID-19, defined as hospitalization, intensive care unit (ICU) admission, or in-hospital death, are higher among racial and ethnic minority groups compared with non-Hispanic White persons. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study included 99 counties within 14 US states participating in the COVID-19-Associated Hospitalization Surveillance Network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
150
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(171 citation statements)
references
References 35 publications
13
150
8
Order By: Relevance
“…Adverse COVID-19 outcomes have been linked to the ethnic origin of the population under study and its socio-economic characteristics; this has also been associated with the presence of vitamin D deficiency. Asians, African Americans, and ethnic minorities are at an increased risk of mortality from COVID-19 ( 34 ). This may partly be due to a decrease in the production of vitamin D dependent on UV rays.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse COVID-19 outcomes have been linked to the ethnic origin of the population under study and its socio-economic characteristics; this has also been associated with the presence of vitamin D deficiency. Asians, African Americans, and ethnic minorities are at an increased risk of mortality from COVID-19 ( 34 ). This may partly be due to a decrease in the production of vitamin D dependent on UV rays.…”
Section: Discussionmentioning
confidence: 99%
“…Our combined use of logistic regression and random forest analyses, as applied to this very large Medicare population, allowed us to further assess the current CDC listing of clinical and socio-demographic risk factors for severe COVID-19 [30,31]. Logistic regression and random forest analyses provide two different perspectives: the odds ratios from the logistic regression help identify individual risk while the Feature Importance from the random forest analyses identified the most important variables for predicting severe COVID-19 outcomes at the population-level for the entire cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we evaluated our model real-time in PUI patients seeking acute care in ED after the score became available in the EHR and the model performance remained strong. The difference in ICU admission rate, ventilator use, and mortality rate between the training set and the temporal, PUI, and real-time validation sets can be explained by the temporal improvement in COVID-19 patients’ outcomes that was noted in other studies [ 4 , 32 , 33 ]. The COVID-19 ICU admission and patient survival improved in our study over time as it did in other reports, perhaps because of better understating of the diseases and improvement of treatment as the pandemic progresses [ 4 , 33 ] In our study, for a cutoff of 0.1 for COVID-19 severity, our model had a sensitivity of 73.7% and specificity 79.9% in the prospective validation set, 52.2% and 88.1%, respectively in the PUI set, and 78% and 71%, respectively in the real-time validation set.…”
Section: Discussionmentioning
confidence: 84%
“…A multihospital United States (U.S.) based cohort study identified that the 30-day mean risk standardized event rate of hospital mortality and hospice referral among patients with COVID-19 varied from 9% to 16%, with better outcomes occurring in community’s with lower disease prevalence [ 3 ]. A large cross-sectional study found racial and ethnic disparities in rates of COVID-19 hospital and ICU admission and in-hospital mortality in the US [ 4 ].…”
Section: Introductionmentioning
confidence: 99%